2003
DOI: 10.1021/jf030378r
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Content in Meat of Some Poultry and Fish Species As Influenced by Live Weight and Total Lipid Content

Abstract: Total cholesterol content in 24 fillets (F) of males and females of common carp, 35 samples of male chicken breast meat (BM) and thigh meat (TM), and 48 samples of male turkey BM and TM, respectively, was determined by high-performance liquid chromatography after total lipid (TL) extraction using n-hexane/2-propanol mixture. Cholesterol content in male carp fillets (77.6 mg/100 g) was higher (P < 0.001) in comparison with females (69.4 mg/100 g). Irrespective of the sex differences, cholesterol content increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
5
20
0
1
Order By: Relevance
“…Mean values of cholesterol found in drumstick in the present study (55 mg/100 g) are similar to those found by Konjufca et al (1997) and Komprda et al (2003). Comparison of the results between present study and literature are very diff icult because the analytical method used to measure cholesterol content in various animal tissues depends strongly on the method of determination (Komprda et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Mean values of cholesterol found in drumstick in the present study (55 mg/100 g) are similar to those found by Konjufca et al (1997) and Komprda et al (2003). Comparison of the results between present study and literature are very diff icult because the analytical method used to measure cholesterol content in various animal tissues depends strongly on the method of determination (Komprda et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Comparison of the results between present study and literature are very diff icult because the analytical method used to measure cholesterol content in various animal tissues depends strongly on the method of determination (Komprda et al, 2003). The daily intake of cholesterol currently recommended must not exceed 300 mg (www.nal.usda.gov/fnic/ foodcomp/search).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, cholesterol can fluctuate depending on the level of sex hormones, which a precursor it is. Komprda et al (2003) analyzed the content of the cholesterol in the meat of males and females of carp harvested from Czech ponds and showed that the cholesterol content was significantly higher (P<0.001) in the mat of males (77.6 mg·100 g ). The differences could be due to different levels of sex hormones in the serum of fish of different sexes.…”
Section: Resultsmentioning
confidence: 99%
“…The total cholesterol content in the meat of fish depends on the species, age, sex, spawning cycle, harvesting period and geographical location of the reservoir (Donmez, 2009;Komprda et al, 2003;Piironen et al, 2002;Živković et al, 2002). Bieniarz et al (2001) confirmed a statistically significant differences in the total cholesterol content in the meat of some line of carp (Cyprinus carpio L.) depending on the age and season.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that total lipid content in raw skinless chicken breast (1.2%) was less than in raw chicken breast with skin (8.9%), (Pereira and Vicente, 2013;Komprda et al, 2003). Additionally, signifi cant differences in cholesterol and lipid content have reported between muscle types due to differences in their fi ber types (Bragagnolo, 2009).…”
Section: Cholesterol and Total Lipid Content In Broiler Meatmentioning
confidence: 99%